Understanding Early Injury Management Using the Rice Method in Futsal Extracurricular Players (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
There are quite a lot of inter-school futsal tournaments in Jambi City, including those participated by the futsal team of SMA Negeri 11 Jambi City. However, in its implementation, it was still found that injury management was less than optimal, mainly due to the lack of first aid facilities and players' knowledge regarding early injury management. This study aims to determine the level of understanding of extracurricular futsal players at SMA N 11 Jambi City regarding early injury management using the RICE (Rest, Ice, Compression, Elevation) method. This study is a descriptive study with a quantitative approach. The sample used a total sampling technique involving all 21 extracurricular futsal members. The results showed that the players' understanding of the translation indicator was in the good category at 78%, the interpretation indicator was 76% (good category), and the extrapolation indicator was 80% (good category). Overall, the players' level of understanding regarding early injury management using the RICE method was included in the good category with an average percentage of 78%. Thus, although understanding is considered good, there are still some players who have not mastered proper injury management, so education and the provision of adequate injury management facilities are needed.